Anaphoric Stylistics of Sūrat Ar-Raḥmān [55]: Gorys Keraf's Framework on Repetition - Setiadi, Fadlan Masykura; Daulay, Irmasani; Balqis, Nur; Elassali, Fatima Ezzahraa (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This study aimed to analyze the forms and rhetorical functions of anaphoric stylistic devices in Sūrat ar-Raḥmān [55] through a modern stylistic approach. The research specifically examines the repetitive expression “Fa-bi`ayyi ālā’i rabbikumā tukażżibān”, which appears thirty-one times throughout the sūrah and constitutes one of the most prominent examples of Qur’ānic repetition. This study employed a qualitative descriptive, this study applies textual analysis based on Gorys Keraf’s stylistic theory, particularly his framework of figurative language and rhetorical repetition, integrated with the classical concept of Qur’ānic rhetoric (balāghah). The scope of the analysis is limited to five major verse clusters in Sūrat ar-Raḥmān that contain dominant repetitive structures and thematic coherence. The findings reveal three principal forms of anaphora, namely lexical anaphora, clausal anaphora, and imperative-rhetorical anaphora. In total, thirty-one repetitive anaphoric structures were identified and systematically classified according to their linguistic and rhetorical characteristics. These repetitive forms function as instruments of ta’kīd (semantic emphasis), generators of rhythmic and psycholinguistic effects, and rhetorical mechanisms that strengthen emotional engagement and spiritual reflection. The study confirms that repetition in the Qur’ān does not represent linguistic redundancy, but rather constitutes a deliberate divine rhetorical strategy that reinforces meaning, aesthetic harmony, and theological consciousness. This study contributes to the field of Qur’ānic stylistics by providing a systematic classification of anaphoric structures and by demonstrating the relevance of modern stylistic theory in analyzing classical Arabic sacred discourse.